Plants from the park : Establishing community harvesting of plants as a conservation tool at Bwindi Impenetrable and Mgahinga National Parks, Uganda - Wild, R G (Department of Biological Sciences, 2014)
It is now accepted that communities surrounding national parks in developing countries should benefit from conservation if the parks, and their constituent biodiversity, are to have a secure long-term future. It has also been accepted as morally questionable for communities living next to parks to pay the costs for national and international biodiversity conservation, and at the same time being excluded from any level of decision making regarding the management of those parks. Strategies to achieve conservation with equity include community involvement in park management and mechanisms to share conservation benefits.